Green foxtail (Setaria viridis) resistance to acetolactate synthase inhibitors - Volenberg, D.S.; Stoltenberg, D.E.; Boerboom, C.M. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2002)
Green foxtail (Setaria viridis) plants putatively resistant to acetolactate synthase (ALS) inhibitors were identified in a Wisconsin USA no-tillage soybean (Glycine max) field in 1999. Resistance to imidazolinone and sulfonylurea herbicides was characterized at the whole-plant level and enzyme level. Three- to four-leaf stage green foxtail plants were 1020, 53, and 6.5-fold resistant to imazethapyr, imazamox, and nicosulfuron, respectively, compared to susceptible plants. In vivo ALS was 1300 and 1.7-fold resistant to imazethapyr and nicosulfuron, respectively. These results suggested that this green foxtail accession was highly resistant to imazethapyr and imazamox, and that resistance was associated with an insensitive ALS enzyme.